Factors Associated With Post Placental Intrauterine Device (IUD) Use - Widiastini, Luh Putu; Karuniadi, I Gusti Agung Manik; Dewi, Luh Gede Susila (Poltekkes Kemenkes Jakarta III, 2024)
An intrauterine device (IUD) is the right choice for post-placental contraception because it has high effectiveness, reversible, long-term effects, and low side effects. Factors that cause low IUD use are knowledge, the role of health workers, husband support and psychological factors such as anxiety during insertion, side effects and trauma during past insertion. The study aims to determine the factors associated with using post-placental IUDs at Mangusada Hospital. This study used an analytic cross-sectional design. The sampling technique used purposive sampling, with 66 respondents, in September and October 2023. Data analysis using the Chi-square test, Mann Whitney and logistic regression with 95% CI and p-value significance <0.05. The results showed the p-value of knowledge, husband support, health worker information and anxiety <0.05, which means there is a relationship between knowledge, husband support, health worker information and anxiety on the use of post-placental IUD. The results of multivariate analysis showed that one sub-variable (husband's support) was most associated with post-placental IUD use with a p-value of 0.00 <0.05. Conclusion: Husband support partially relates to post-placental IUD use at Mangusada Hospital.